Analysis of the Level of Teacher Creativity in Physical Education Learning Outcomes - Abdul Wahid; Anggi Setia Lengkana; Dewi Susilawati (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
This study aims to determine the level of teacher creativity in physical education learning outcomes. This study uses qualitative research methods with a triangulation process, namely observation, interviews and questionnaires. The research subjects in this study were PJOK teachers, PJOK Peer teachers, school principals, representatives of students in grades IV, V, VI. From the results of research in the field, several conclusions regarding teacher creativity were revealed; First, it shows that learning media modifications affect student learning efficiency. Second, participation and response to learning media affect students' enthusiasm for learning. Third, the 2013 curriculum and independence affect the efficiency of learning outcomes. Fourth, school facilities and infrastructure affect teacher creativity. Fifth, the good social environment of the surrounding community will support the learning process of Kudanguyah Elementary School students.